Tindakan Manusia Menurut Ibnu Bajjah dalam Kitab Tadbir al-Mutawahhid - Hestyana Widya Pangesti; Rahmat Hidayat (KOLONI, 2023)
Ethics comes from the Greek "ethos" which means customs, human habits in behavior. Ethics is a branch of philosophy that studies human actions and behavior. Some philosophers have explained about ethics, one of them is Ibn Bajjah, who was the first philosopher in the Western Islamic region, Andalusia. He explained some human actions and behaviors in his work Tadbir al-Mutawahhid, for example related to politics. Ibn Bajjah's theory is different from Al-Farabi, because Ibn Bajjah chose to explain about humans who are alone living and acting in communities, he did not direct his political philosophy for leadership theory. In this case, the research is aimed at examining Ibnu Bajjah’s views on actual human actions or behavior. So the aim of this research is to find how Ibnu Bajjah views human action in the works of Tadbir al-Mutawahhid. This research is a library research, whose primary data comes from Kitab Tadbir al-Mutawahhid, while secondary data comes from scientific journals and books related to the research topic. The collected data were analyzed using the descriptive-analytical method. The results of this study indicate that a mutawahhid (loner) according to Ibn Bajjah must always be in contact with the community. The consequence that a person undergoes is that he must be able to control himself, control his lusts so as not to be dragged into the low deeds of society. So that humans in acting can make choices based on their intellect and thoughts. Human intelligence is the difference between humans and other creatures, including animals.